2000
DOI: 10.1523/jneurosci.20-19-07377.2000
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Proliferation, Survival, and Dopaminergic Differentiation of CNS Precursors in Lowered Oxygen

Abstract: Standard cell culture systems impose environmental oxygen (O 2 ) levels of 20%, whereas actual tissue O 2 levels in both developing and adult brain are an order of magnitude lower. To address whether proliferation and differentiation of CNS precursors in vitro are influenced by the O 2 environment, we analyzed embryonic day 12 rat mesencephalic precursor cells in traditional cultures with 20% O 2 and in lowered O 2 (3 Ϯ 2%). Proliferation was promoted and apoptosis was reduced when cells were grown in lowered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
531
14
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(585 citation statements)
references
References 47 publications
37
531
14
3
Order By: Relevance
“…The present results suggest that Apocynin and 5-HD act by stimulating differentiation of mesencephalic precursors toward the DA phenotype. The results are consistent with those of previous studies, which have suggested that the redox state modulates differentiation of mesencephalic precursors (Studer et al, 2000;Rodriguez-Pallares et al, 2001Tsatmali et al, 2005), and with those of studies that have suggested that ROS levels affect the phenotype of cells in culture (Li et al, 2006;Xiao et al, 2009), including neurons (Tsatmali et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present results suggest that Apocynin and 5-HD act by stimulating differentiation of mesencephalic precursors toward the DA phenotype. The results are consistent with those of previous studies, which have suggested that the redox state modulates differentiation of mesencephalic precursors (Studer et al, 2000;Rodriguez-Pallares et al, 2001Tsatmali et al, 2005), and with those of studies that have suggested that ROS levels affect the phenotype of cells in culture (Li et al, 2006;Xiao et al, 2009), including neurons (Tsatmali et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…It is known that the number of proliferating DAergic precursors in culture is maximal during the first week and decreases sharply thereafter (Bouvier and Mytilineou, 1995). The number of proliferating cells further decreases after induction of the differentiation, as expected after withdrawal of the mitogens from the cell culture (Studer et al, 2000;Ebert et al, 2008). Several previous studies have suggested that intracellular levels of ROS modulate neuronal differentiation, and it has been observed that cell fractions exhibiting low levels of ROS contain proliferative progenitor cells, while newly generated neurons express high levels of ROS (Katoh et al, 1997;Goldsmit et al, 2001;Wang et al, 2007;Tsatmali et al, 2005); this was also confirmed in the present study by DHE labeling.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…For example, hematopoietic stem cells are maintained in hypoxic niches in bone marrow (Parmar et al, 2007). Interestingly, hypoxia also prevents the differentiation of neural stem cells and promotes the maintenance of self-renewal potential of embryonic stem (ES) cells (Studer et al, 2000;Marrison et al, 2000;Ezashi et al, 2005;Santilli et al, 2010). In addition, restricted oxygen concentrations have been shown to enhance the production of induced pluripotent stem cells (iPSC) (Yoshida et al, 2009).…”
Section: Hypoxic Responses In Glioblastoma Stem Cellsmentioning
confidence: 99%
“…Indeed, in vitro, EPO increases proliferation and differentiation of neural stem cells or neuroblasts into neurons (Studer et al, 2000;Shingo et al, 2001). In vivo, EPO administered into the lateral ventricles of the adult mouse increases the number of newly generated cells migrating to the olfactory bulb and the number of new olfactory bulb interneurons (Shingo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%